2018
DOI: 10.2320/matertrans.m2017255
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Soldering of Low-Ag SAC Lead-Free Solder Paste at Low-Temperature

Abstract: SAC0307 (Sn-0.3mass%Ag-0.7mass%Cu) lead-free solder pastes were used to complete Cu/Cu joint by ultrasonic-assisted. Effect of nano-Ni particles and temperature on the performance of joint by ultrasonic-assisted with lead-free solder paste were investigated. The experimental results have shown that interfacial IMC of joint with SACP were typical scallop-type, but the type of interfacial IMC were serrated and became smoother after added nano-Ni particles. The IMC thickness was not more than 6.00 μm and the IMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Nowadays, ultrasonic soldering technology has aroused ever-increasing attention and intense efforts (Zulkifli et al, 2019). Especially in electronic packaging industry, research mainly focus on metal substrates such as Al (Guo et al, 2017), Cu (Gan et al, 2019), ceramic materials igure 2 Soldering seam of joints by different ultrasonic loading degrees (Kolenak et al, 2021) or soldering of metals and ceramics (Yi et al, 2022;Li et al, 2022a). , the maximum shear strength of joint could reach 22.76 MPa under a 30 s ultrasonic-assisted time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, ultrasonic soldering technology has aroused ever-increasing attention and intense efforts (Zulkifli et al, 2019). Especially in electronic packaging industry, research mainly focus on metal substrates such as Al (Guo et al, 2017), Cu (Gan et al, 2019), ceramic materials igure 2 Soldering seam of joints by different ultrasonic loading degrees (Kolenak et al, 2021) or soldering of metals and ceramics (Yi et al, 2022;Li et al, 2022a). , the maximum shear strength of joint could reach 22.76 MPa under a 30 s ultrasonic-assisted time.…”
Section: Introductionmentioning
confidence: 99%
“…Gan et al (2021bGan et al ( , 2020 adopted a new approach by mixing 45 mm Zn particles with 20-38mm SAC0307 particles to form a sold-filled joint, successfully realizing the low-temperature soldering of Cu-Cu at 220°C by ultrasound-assisted soldering, where the shear strength of joint could reach 34.2 MPa. In addition, 0.5% Ni nanoparticles (80 nm) were added to the SAC0307 particles to improve the joint performance, and the Cu-Cu joint with shear strength up to 41.20 MPa was obtained under the conditions of 5 s and 210°C with ultrasonic-assisted soldering (Gan et al, 2018). Jiang et al (2021) has successfully realized the high-quality soldering of Cu and Al at a low temperature of 220°C by using the dual ultrasonic-assisted technology.…”
Section: Introductionmentioning
confidence: 99%
“…However, investigations have found that, as the Ag content decreases, SAC solders also have some disadvantages, such as a high melting temperature, thick intermetallic compounds (IMCs) and insufficient oxidation resistance characteristics, which can lead to poor reliabilities of solder joints (Ma et al, 2019;Jing et al, 2017). A lot of research has been conducted to solve these problems (Sun et al, 2016;Gan et al, 2013aGan et al, , 2013bGan et al, 2018). However, these researches had little effect in improving solder performance, and, for the solderability and the melting temperature of the solder, it was difficult to achieve satisfactory results.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies had little effect in improving the solder performance, solderability and the melting temperature (Jing et al, 2017;Ma et al, 2017; The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0954-0911.htm Zhao et al, 2016). Recently, several different methods were proposed to decrease soldering temperatures including using composite solder (mixed by high-and low-temperature solder) (Shen et al, 2019), nanosolders (Roshanghias et al, 2015), nanoparticle reinforced composite solder or solder paste (Rajendran et al, 2022;Min et al, 2019), nanoparticle reinforced solders or solder pastes and low-temperature stir soldering simultaneously (Gan et al, 2013a;Gan et al, 2013b;Gan et al, 2013c), nanoparticle reinforced solder or solder paste and ultrasonic soldering simultaneously (Gan et al, 2019;Gan et al, 2018;Gan et al, 2017) and so on. But all needed flux.…”
Section: Introductionmentioning
confidence: 99%